Optical Properties Degradation of Organolead Halide Perovskite with Lead Devired from Solder Wire - Putri Pratiwi (Jurnal Teknik Mesin, 2017)
Organolead halideperovskite material was used as the most common light-harvesting active layer in perovskite solar cell. This material is the most promising material in photovoltaic technology due to its fastest-advancing power conversion efficiency (PCE) to date. The PCE has increased up to 22.1 % only six years after it was discovered in 2009. In our last research, we synthesized and fabricated perovskite solar cell using CH3NH3PbI(3-x)Clx material as light-harvesting active layer. We extract lead from solder wire to produce PbCl2 powder. This powder was used as basic substance for organolead halide perovskite material. CH3NH3PbI(3-x)Clx solution produced by reacting CH3NH3 with PbCl2 powder in DMF (Anhydrous N,N-Dhymethilformamide) by using solution based method. Based on device performance characterization, we conclude that solder wire is suitable enough for fabricating perovskite solar cell. They have identical characteristic compared to commercial lead. However, both perovskite solar cell using lead from solder wire and commercial lead’s performance are smaller than published solar cell’s efficiency. Therefore, in this study we investigate that degradation affected perovskite material performance, especially physical appearance and absorbance characteristic.